Operational Potentialities and Basic Structures of Photoelectric Zero-Detectors - V. B. Yarzhembitski; L. I. Shadurskaya; A. I. Svistun (Наука и техника)
The main types of basic structures of photoelectric zero-detectors which we have named, as paraphase photodetectors are considered in the paper. The paper gives analysis of operational principles, output characteristics and possible fields of application of such devices. The basic advantages of paraphase photodetectors are specified in the paper.